Central versus Low-Lying Umbilical Venous Catheters: A Multicenter Study of Practices and Complications - El Ters, Nathalie; Claassen, Colleen; Lancaster, Thomas; Barnette, Alan; Eldridge, Whitney; Yazigi, Flora; Brar, Komalpreet; Herco, Maja; Rogowski, Lauren; Strand, Marya; Vachharajani, Akshaya (American Journal of Perinatology, 2019)
Objectives Conventional neonatology practice is to place umbilical venous catheters (UVCs) in central position and to limit the use of low-lying catheters. Our objectives were to describe the practices and complications associated with UVCs and to evaluate the type of infusates used with either UVC position.Study Design A retrospective chart review was performed at four neonatal intensive care units to identify neonates who underwent UVC placement over a 2-year period. Infant demographics, UVC position, catheter days, fluid and medication characteristics, and specific complications were extracted.Results A total of 2,011 neonates who underwent UVC placement were identified during the 2-year period. Of these, 641 UVCs (31.9%) were identified in the low-lying position. Centrally positioned UVCs were associated with lower gestational age and were left in situ for a longer duration than low-lying UVCs. Infusions of hyperosmolar solutions and vasopressors were significantly higher in central UVCs, though they were used in a significant number of low-lying UVCs. Complications, while not statistically different, were three times higher in low-lying UVCs.Conclusion Despite conventional teaching, low-lying UVCs were used in nearly one-third of infants in this cohort. Parenteral nutrition, antibiotics, and vasopressors were infused through central and low-lying UVCs. There was no statistically significant difference in complication rates between UVC positions.
Keywords: umbilical venous catheters; central; low-lying; infusates; complications